Sustainable organisational procurement: a progressive approach towards sustainable development. (28th July 2005) - Grob, Suzanne; McGregor, Ian
This paper examines the relationship between organisations and their ability to contribute to sustainable development through sustainable procurement. Organisations, particularly corporations and government, command an increasingly powerful influence on the economy and society and are required to serve a wide range of stakeholders, including the community, shareholders, employees, customers, and suppliers. In total, this sector has the potential to exercise substantial power because of the enormous value of its purchasing expenditure. This paper explores the progress of organisations towards sustainable procurement as part of moving towards becoming a sustainable organisation. To demonstrate this transition, this paper uses a framework based on the phase model of sustainability proposed in Organizational Change for Corporate Sustainability by Dunphy et al. (2003). This framework outlines six phases in a progression towards sustainable procurement (rejection, nonresponsiveness, compliance, efficiency, strategic proactivity, sustainable organisation) as part of moving towards becoming a sustainable organisation.